Voyages of Whales through Galician and Irish Contemporary Poetry: Gender, Empowerment and Extinction - Palacios, Manuela (Madrygal. Revista de Estudios Gallegos, 2017)
The present article analyses the literary motif of the whale in Galician and Irish contemporary poetry and makes use of an ecofeminist frame that brings together recent debates in ecocriticism and feminism. The analysis of the interrelated oppression of women and nature leads us to appraise the motif of the whale beyond the trope of feminine empowerment so as to estimate the effect of the cetaceans’ extinction and the role of whaling fisheries from Galicia and Ireland. Contemporary poetry in these two communities puts forward figurative transgeneses of whales and humans so that we may not forget our animal nature and may recognise the other inside us. We find that this poetry deprecates phenomena such as the spectacularization of nature and the exploitation of its resources to the point of extermination,and promotes instead empathy and respect for the other’s relative difference. This article also discusses the different use of the motif of the whale in each literary system, both regarding its visibility and its more or less ecological or allegorical dimension.